Increasing LTE-Advanced Network Capacity Using The Inter-band Carrier Aggregation (Downlink Side) Method - Fadli Kusuma; Hasanah Putri (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2020)
According to the identification of the Operating Support System (OSS) by the Smartfren cellular operator in the Central Bandung area, six sites are found to have high traffic capacity with the physical resource block (PRb) percentage of 82.6 %. The use of PRb > 80 % is included in the warning indicator 2 based on the operator’s standards. It is also strengthened by the condition of the existing sites with the average Reference Signal Receive Power (RSRP) of -103.3 dBm, Signal to Interference Noise Ratio (SINR) of 6.28 dB, and throughput of 27.78 Mbps, thus resulting in non-optimal network performance in the area. Therefore, in this study, the inter-band Carrier Aggregation (CA) was applied by combining the 40 Time Division Duplex (TDD) band (2300 MHz) and band 5 Frequency Division Duplex (FDD) (850 MHz). One of the advantages of applying this method is that it can increase the user network capacity by maximizing the resources owned by the operator. The predetermined scenario taking into account the initial network condition indicated a decrease in the PRb percentage by 44.50 % and an increase in the average RSRP value by 12.8 dBm, SINR by 5.14 dB, and throughput by 34.59 Mbps.